2023
DOI: 10.3390/buildings13102613
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of the Influence of Bearing Plate Position on the Bearing Performance of Soil around the CEP Antipull Force Double Pile

Yongmei Qian,
Lin Sun,
Lishuang Ai
et al.

Abstract: With the development of large-scale projects such as high-rise buildings, deep-sea platforms, bridges, etc., these construction facilities are affected by many factors such as environment and geological conditions, which put forward higher requirements for pile-bearing capacity. Compared with the straight-hole grouted piles, the CEP (concrete expanded-plate) piles have an increased bearing plate, which has stronger resistance to pullout under the action of axial tension. The location of the bearing plate is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…At present, a large number of theoretical and experimental studies have been carried out on the bearing capacity of single NT-CEP piles and soil failure around piles, and systematic research results have been achieved, such as the influence degree of different parameters on bearing capacity [8], the research on bearing capacity calculation formula [9], etc. However, research on NT-CEP pile groups is relatively lacking, which limits the development of NT-CEP piles [10,11]. The plate position was the main factor influencing the NT-CEP pilebearing capacity, especially in the pile group layout.…”
Section: Introductionmentioning
confidence: 99%
“…At present, a large number of theoretical and experimental studies have been carried out on the bearing capacity of single NT-CEP piles and soil failure around piles, and systematic research results have been achieved, such as the influence degree of different parameters on bearing capacity [8], the research on bearing capacity calculation formula [9], etc. However, research on NT-CEP pile groups is relatively lacking, which limits the development of NT-CEP piles [10,11]. The plate position was the main factor influencing the NT-CEP pilebearing capacity, especially in the pile group layout.…”
Section: Introductionmentioning
confidence: 99%
“…With more studies conducted on pile foundations, the research object has shifted from single piles to group piles. Yalcin et al [5,6] studied the bearing performance of flexible piles and small group piles under eccentric and inclined loads and noted that the ultimate bearing capacity of piles depends on the eccentricity and inclination of loads, as well as the ratio of the upper layer thickness to the pile burying depth. Wang et al [7] studied the bearing capacity of double piles under static pressure in sandy soil foundations through laboratory model tests and reported that the bearing capacity of static piles was mainly affected by the pile length and static pressure velocity, and the radial stress of piles under different pile lengths increased nonlinearly with depth and gradually converged to the passive earth pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance and monitoring of the condition of the structure and its load-bearing elements are performed to increase the bridge life resource [4,5]. Also, one of the options for increasing the bearing capacity and bridge service life can be the selection of rational geometry and/or location of its important elements, including the rational geometry of the sliding layer [6], location of the bearing plate of a CEP pile [7], and rational geometry of lubricant recesses [8].…”
Section: Introduction 1research Objectivesmentioning
confidence: 99%